Moringa oleifera Lam and its Therapeutic Effects in Immune Disorders - Xiao, Xiao; Wang, Jue; Meng, Chen; Liang, Weibo; Wang, Tao; Zhou, Bin; Wang, Yanyun; Luo, Xiaolei; Gao, Linbo; Zhang, Lin (Frontiers in Pharmacology, 2020)
Moringa oleifera Lamarck, a native plant tropical forests of India, is characterized by its versatile application as a food additive and supplement therapy. Accumulating evidence shows that Moringa oleifera Lamarck plays a critical role in immune-related diseases. In this review, we cover the history, constituents, edibility, and general medicinal value of Moringa oleifera Lamarck. The effects of Moringa oleifera Lamarck in treating immune disorders are discussed in detail. Moringa oleifera Lamarck can not only eliminate pathogens, including bacteria, fungi, viruses, and parasites, but also inhibits chronic inflammation, such as in asthma, ulcerative colitis, and metabolic diseases. Additionally, Moringa oleifera Lamarck can attenuate physical and chemical irritation-induced immune disorders, such as metal intoxication, drug side effects, or even the adverse effect of food additives. Autoimmune diseases, like rheumatoid arthritis, atopic dermatitis, and multiple sclerosis, can also be inhibited by Moringa oleifera Lamarck. Collectively, Moringa oleifera Lamarck, with its multiple immune regulatory bioactivities and few side effects, has a marked potential to treat immune disorders.